2016
DOI: 10.20471/acc.2016.55.04.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Delivery and Episiotomy on the Emergence of Urinary Incontinence in Women: Review of Literature

Abstract: SUMMARY -Episiotomy is obstetric procedure during which the incision extends the vestibule of the vagina during the second stage of labor. Episiotomy was extensively spread with gradual increase of rates in the fi rst half of the 20 th century and was performed mediolaterally in all nulliparous women with the idea to protect fetal head from trauma and pelvic fl oor from injuries. However, reports claiming that episiotomy had no such benefi ts were published. It was shown that routine mediolateral episiotomy di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
(95 reference statements)
0
7
0
1
Order By: Relevance
“…20 The findings of previous studies on the association between episiotomy and UI after delivery are inconsistent. While some studies suggested increased frequency and intensity of the complaint of postpartum UI in the presence of episiotomy, 21,22 others concluded that the procedure is not associated with the dysfunction. 4,5 Variations in the instruments used to define UI in the characteristics of the studied population (adult age group) and in the event observation period may explain the divergence between the results.…”
Section: Discussionmentioning
confidence: 99%
“…20 The findings of previous studies on the association between episiotomy and UI after delivery are inconsistent. While some studies suggested increased frequency and intensity of the complaint of postpartum UI in the presence of episiotomy, 21,22 others concluded that the procedure is not associated with the dysfunction. 4,5 Variations in the instruments used to define UI in the characteristics of the studied population (adult age group) and in the event observation period may explain the divergence between the results.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that perineum damage during labor, irrespective of its underlying cause, increases the risk of incontinence occurrence. This assumption is further confirmed by the fact that routine episiotomy during labor, as incontinence prophylaxis, is controversial amongst vari-ous authors [10,[19][20][21][22]. Presumptions about the protective effect of surgical labor on urinary incontinence on the basis of the accumulated data have to be attempted very carefully as it is not clear whether urinary incontinence occurred during pregnancy, which ended in Caesarean section due to various causes.…”
Section: Discussionmentioning
confidence: 99%
“…A urodynamic test is performed when the diagnosis is doubtful, for diagnostic confi rmation, and the patient will undergo a surgical therapy process. This is justifi cation because of research shows low morbidity and cost reasons 14 .…”
Section: Introductionmentioning
confidence: 96%
“…Of these patients, 10% -30% are found to have symptoms of detrusor instability (alone or together with SUI). Rare events that can cause SUI symptoms are urethral diverticulum, genitourinary fi stula, ectopic ureter, and urethral instability 14 . Clinics must recognize occured clinical situations that diagnoses SUI based solely on clinical symptoms still have a range of uncertainties.…”
Section: Introductionmentioning
confidence: 99%